Preparation method of negative electrode material, battery negative electrode and battery
Through electrospinning technology, hard carbon, carbonized natural graphite and carbonized artificial graphite mixed materials are prepared into nanofiber negative electrode materials, which solves the problems of natural graphite in fast charging and stability, and achieves efficient battery performance improvement and cost reduction.
Patent Information
- Application Number
- CN202411319691.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
AI Technical Summary
Natural graphite performs poorly in fast charging and stability, with existing improvement methods being costly or poorly performant.
Electrospinning is prepared by using a mixture of hard carbon, carbonized natural graphite and carbonized artificial graphite. The nanofiber negative electrode material is formed through preoxidation and carbonization treatment, and the spinning solution is formed in combination with polyacrylonitrile to improve the conductivity and cycle stability of the material. .
The fast charging performance and cycle stability of the negative electrode of the battery are improved, the preparation cost is reduced, and the conductivity and stability of the material are significantly improved.
Smart Images

Figure BDA0005054065220000071
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a method for preparing a negative electrode material, a battery negative electrode and a battery. Background Art
[0002] Natural graphite has attracted more and more attention due to its high capacity and low price, but its structure has large interlayer spacing and many impurities, resulting in poor fast charging and stability. In order to improve its fast charging performance and stability, most of the methods currently used are to add graphitization and carbon coating processes to the original process of natural graphite, or directly use high-fast charging artificial graphite, which is costly and not environmentally friendly; or directly mix natural graphite with artificial graphite. Although this method can improve the fast charging performance of the material to a certain extent, the conductivity and cycle stability of the material are poor. Summary of the invention
[0003] Based on this, it is necessary to provide a method for preparing a negative electrode material, a battery negative electrode and a battery to address the above technical problems, so as to solve the fast charging performance of natural graphite while also improving its cycle stability.
[0004] The first aspect of the present application provides a method for preparing a negative electrode material, comprising:
[0005] Physically mixing hard carbon, carbonized natural graphite, and carbonized artificial graphite to obtain a graphite mixed material;
[0006] Adding graphite mixed material and polyacrylonitrile into water and stirring and mixing to obtain a spinning solution;
[0007] The fiber film is obtained by electrospinning the spinning solution;
[0008] The fiber film is placed at 180°C to 250°C and pre-oxidized in an air atmosphere to make it cross-linked;
[0009] The pre-oxidized fiber film is slowly heated to 1000°C to 2500°C in an inert atmosphere for carbonization treatment and then naturally cooled to obtain a nanofiber negative electrode material.
[0010] The surfaces of natural graphite and artificial graphite are carbon-coated, sintered and carbonized at a high temperature of 1000° C. to 1500° C., and then demagnetized to obtain carbonized natural graphite and artificial graphite. This is a prior art and will not be described in detail here.
[0011] Placing the fiber film at 180℃-250℃ can achieve a quick and uniform reaction with air to achieve pre-oxidation. Slowly heating the pre-oxidized fiber film to 1000℃-2500℃ in an inert atmosphere for carbonization makes the material more stable.
[0012] In one embodiment, the mass ratio of carbonized natural graphite, carbonized artificial graphite and hard carbon in the graphite mixed material is 60-70 parts of carbonized natural graphite, 20-30 parts of carbonized artificial graphite and 1-10 parts of hard carbon. Preferably, the mass ratio of carbonized natural graphite, carbonized artificial graphite and hard carbon in the graphite mixed material is 65 parts of carbonized natural graphite, 25 parts of carbonized artificial graphite and 5 parts of hard carbon, which helps to improve battery performance.
[0013] In one embodiment, the particle size D50 of the carbonized natural graphite is 9-12 μm, which can ensure the transmission speed of lithium ions and improve the dynamic performance of natural graphite.
[0014] In one embodiment, the particle size D50 of the carbonized artificial graphite is 13-16 μm, which can ensure the transmission speed of lithium ions and improve the dynamic performance of the artificial graphite.
[0015] In one embodiment, in the spinning solution, the concentration of carbonized natural graphite, carbonized artificial graphite and hard carbon graphite mixed material in the spinning solution by weight volume ratio is 65% to 95% (w / v), and the concentration of polyacrylonitrile PAN in the spinning solution by weight volume ratio is 5% to 35% (w / v). That is to say, the weight of the graphite mixed material contained in each 100 ml solution is 65-95 mg and the weight of polyacrylonitrile PAN is 5-35 mg. Preferably, in the spinning solution, the concentration of carbonized natural graphite, carbonized artificial graphite and hard carbon graphite mixed material in the spinning solution by weight volume ratio is 80% to 90% (w / v), and the concentration of polyacrylonitrile PAN in the spinning solution by weight volume ratio is 10% to 20% (w / v), so that the performance of the electrostatically spun nanofiber membrane is better, and the conductivity and cycle stability performance of the battery as a negative electrode material are improved.
[0016] In one embodiment, during the electrospinning process using the spinning solution, the flow rate of the spinning solution is controlled to be 0.3-1.5 mL / h.
[0017] In one embodiment, the graphite mixed material and polyacrylonitrile are added to water and stirred for 10 to 20 hours;
[0018] In the process of electrospinning using the spinning solution, the spinning solution is sucked into a syringe with a needle with an inner diameter of 0.3 to 1 mm, and the syringe is placed on a syringe pump to control the flow rate. The distance between the spinneret and the receiving plate is 10 to 25 cm, and the voltage between the plates is 15 to 35 kV. Spinning is carried out at room temperature to obtain a fiber film.
[0019] In one embodiment, the fiber film is placed at 180° C. to 250° C. and pre-oxidized in an air atmosphere so that the cross-linking time is controlled to be 1.5 to 2.5 hours.
[0020] In one embodiment, the pre-oxidized fiber film is slowly heated to 1000° C. to 2500° C. in an inert atmosphere at a rate of 2 to 5° C. / min.
[0021] In one embodiment, the pre-oxidized fiber film is treated at 1000° C. to 2500° C. in an inert atmosphere for 2 to 10 hours.
[0022] The second aspect of the present application also provides a battery negative electrode, which is prepared by the above-mentioned method for preparing the negative electrode material.
[0023] The third aspect of the present application further provides a battery, comprising a battery negative electrode, wherein the battery negative electrode is prepared by the above-mentioned method for preparing the negative electrode material.
[0024] The above introduces the preparation method of the negative electrode material, the battery negative electrode and the battery. The preparation method has a simple process and relatively low cost. The natural graphite, artificial graphite and hard carbon are mixed into a film by an electrospinning method. The artificial graphite has few surface defects and produces few side reactions with the electrolyte. The mixing of a small amount of hard carbon can improve the fast charging capability. The two materials are mixed with natural graphite to improve the fast charging performance and cycle stability of the negative electrode graphite. The electrospinning method is used to improve the fast charging performance of the material while improving the cycle stability of the material. DETAILED DESCRIPTION
[0025] The following is a further description of the preparation method of the negative electrode material, the negative electrode of the battery and the battery of the present invention in conjunction with the embodiments:
[0026] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0027] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0028] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0029] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0030] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0031] Unless otherwise specified, the "parts" described in the present invention are all based on parts by weight.
[0032] The present invention uses an electrostatic spinning method to prepare a graphite mixed material to improve the fast charging performance. The method is simple. Compared with directly mixing carbonized natural graphite with carbonized artificial graphite, it not only improves the fast charging performance, but also improves the cycle stability.
[0033] Example 1
[0034] 600 mg of carbonized natural graphite, 300 mg of artificial graphite and 100 mg of hard carbon were placed in a stirring device for full physical mixing to obtain a graphite mixed material, wherein the natural graphite particle size D50 was 9-12 μm and the artificial graphite particle size D50 was 13-16 μm. 950 mg of the graphite mixed material and 50 mg of polyacrylonitrile PAN were placed in water, and water was added to make the solution 1000 ml. After continuous stirring at room temperature for 15 hours, a uniform and stable spinning solution was formed.
[0035] The spinning solution was sucked into a plastic syringe with a stainless steel needle with an inner diameter of 0.5 mm, and the syringe was placed on a syringe pump to control the flow rate. The distance between the spinneret and the receiving plate was 20 cm, the solution flow rate was 1.0 mL / h, the voltage between the plates was 15-35 kV, and spinning was performed at room temperature to obtain a fiber film.
[0036] The fiber film containing the polymer was removed from the surface of the receiving plate and placed in an air atmosphere at 220°C for 2 hours, and pre-oxidized in the air to make it cross-linked. Then the pre-oxidized fiber sample was treated at high temperature for 6 hours in an inert atmosphere, with a treatment temperature of 2000°C and a heating rate of 4°C / min, and then naturally cooled to room temperature, and finally the negative electrode material of the graphite mixed material nanofiber was obtained. The negative electrode material was used as the negative electrode of the battery to make a battery. The performance of the battery test during the cycle (25°C, 4C / 1C) at room temperature is shown in Table 1.
[0037] Example 2
[0038] 700 mg of carbonized natural graphite, 200 mg of artificial graphite and 10 mg of hard carbon were placed in a stirring device for full physical mixing to obtain a graphite mixed material, wherein the natural graphite particle size D50 was 9-12 μm and the artificial graphite particle size D50 was 13-16 μm. 650 mg of the graphite mixed material and 350 mg of polyacrylonitrile PAN were placed in water, and water was added to make the solution 1000 ml. After continuous stirring at room temperature for 15 hours, a uniform and stable spinning solution was formed.
[0039] The spinning solution was sucked into a plastic syringe with a stainless steel needle with an inner diameter of 0.5 mm, and the syringe was placed on a syringe pump to control the flow rate. The distance between the spinneret and the receiving plate was 20 cm, the solution flow rate was 1.0 mL / h, the voltage between the plates was 15-35 kV, and spinning was performed at room temperature to obtain a fiber film.
[0040] The fiber film containing the polymer was removed from the surface of the receiving plate and placed in an air atmosphere at 220°C for 2 hours, and pre-oxidized in the air to make it cross-linked. Then the pre-oxidized fiber sample was treated at high temperature for 6 hours in an inert atmosphere, with a treatment temperature of 2000°C and a heating rate of 4°C / min, and then naturally cooled to room temperature, and finally the negative electrode material of the graphite mixed material nanofiber was obtained. The negative electrode material was used as the negative electrode of the battery to make a battery test. The performance during the cycle (25°C, 4C / 1C) at room temperature is shown in Table 1.
[0041] Example 3
[0042] 650 mg of carbonized natural graphite, 250 mg of artificial graphite and 50 mg of hard carbon were placed in a stirring device for full physical mixing to obtain a graphite mixed material, wherein the natural graphite particle size D50 was 9-12 μm and the artificial graphite particle size D50 was 13-16 μm. 850 mg of the graphite mixed material and 150 mg of polyacrylonitrile PAN were placed in water, water was added until the solution reached 1000 ml, and a uniform and stable spinning solution was formed after continuous stirring at room temperature for 15 hours.
[0043] The spinning solution was sucked into a plastic syringe with a stainless steel needle with an inner diameter of 0.5 mm, and the syringe was placed on a syringe pump to control the flow rate. The distance between the spinneret and the receiving plate was 20 cm, the solution flow rate was 1.0 mL / h, the voltage between the plates was 15-35 kV, and spinning was performed at room temperature to obtain a fiber film.
[0044] The fiber film containing the polymer was removed from the surface of the receiving plate and placed in an air atmosphere at 220°C for 2 hours, and pre-oxidized in the air to make it cross-linked. Then the pre-oxidized fiber sample was treated at high temperature for 6 hours in an inert atmosphere, with a treatment temperature of 2000°C and a heating rate of 4°C / min, and then naturally cooled to room temperature, and finally the negative electrode material of the graphite mixed material nanofiber was obtained. The negative electrode material was used as the negative electrode of the battery to make a battery test. The performance during the cycle (25°C, 4C / 1C) at room temperature is shown in Table 1.
[0045] Example 4
[0046] 650 mg of carbonized natural graphite, 250 mg of artificial graphite and 50 mg of hard carbon were placed in a stirring device for full physical mixing to obtain a graphite mixed material, wherein the natural graphite particle size D50 was 9-12 μm and the artificial graphite particle size D50 was 13-16 μm. 850 mg of the graphite mixed material and 150 mg of polyacrylonitrile PAN were placed in water, water was added until the solution reached 1000 ml, and a uniform and stable spinning solution was formed after continuous stirring at room temperature for 10 hours.
[0047] The spinning solution was sucked into a plastic syringe with a stainless steel needle of 1 mm inner diameter, and the syringe was placed on a syringe pump to control the flow rate. The distance between the spinneret and the receiving plate was 25 cm, the solution flow rate was 0.3 mL / h, the voltage between the plates was 15-35 kV, and spinning was performed at room temperature to obtain a fiber film.
[0048] The fiber film containing the polymer was removed from the surface of the receiving plate and placed in an air atmosphere at 180°C for 2.5 hours, and pre-oxidized in the air to make it cross-linked. Then the pre-oxidized fiber sample was treated at high temperature for 10 hours in an inert atmosphere, with a treatment temperature of 1000°C and a heating rate of 2°C / min, and then naturally cooled to room temperature, and finally the negative electrode material of the graphite mixed material nanofiber was obtained. The negative electrode material was used as the negative electrode of the battery to make a battery test. The performance during the cycle (25°C, 4C / 1C) at room temperature is shown in Table 1.
[0049] Example 5
[0050] 650 mg of carbonized natural graphite, 250 mg of artificial graphite and 50 mg of hard carbon were placed in a stirring device for full physical mixing to obtain a graphite mixed material, wherein the natural graphite particle size D50 was 9-12 μm and the artificial graphite particle size D50 was 13-16 μm. 850 mg of the graphite mixed material and 150 mg of polyacrylonitrile PAN were placed in water, and water was added until the solution reached 1000 ml. After continuous stirring at room temperature for 20 hours, a uniform and stable spinning solution was formed.
[0051] The spinning solution was sucked into a plastic syringe with a stainless steel needle with an inner diameter of 0.3 mm, and the syringe was placed on a syringe pump to control the flow rate. The distance between the spinneret and the receiving plate was 10 cm, the solution flow rate was 1.5 mL / h, the voltage between the plates was 15-35 kV, and spinning was performed at room temperature to obtain a fiber film.
[0052] The fiber film containing the polymer was removed from the surface of the receiving plate and placed in an air atmosphere at 250°C for 1.5 hours, and pre-oxidized in the air to make it cross-linked. Then the pre-oxidized fiber sample was treated at high temperature for 2 hours in an inert atmosphere, with a treatment temperature of 2500°C and a heating rate of 5°C / min, and then naturally cooled to room temperature, and finally the negative electrode material of the graphite mixed material nanofiber was obtained. The negative electrode material was used as the negative electrode of the battery to make a battery test. The performance during the cycle (25°C, 4C / 1C) at room temperature is shown in Table 1.
[0053] Comparative Example 1
[0054] The battery was made using natural graphite as the negative electrode, and the performance during the cycle at room temperature (25°C, 4C / 1C) was tested, see Table 1.
[0055] Comparative Example 2
[0056] A battery was made using graphitized and carbonized natural graphite as the battery negative electrode, and the performance during the cycle at room temperature (25°C, 4C / 1C) was tested, see Table 1.
[0057] Comparative Example 3
[0058] A battery was made using artificial graphite as the negative electrode, and the performance during the cycle at room temperature (25°C, 4C / 1C) was tested, see Table 1.
[0059] Comparative Example 4
[0060] A battery was made by using a mixture of carbonized natural graphite and artificial graphite as the negative electrode, and the performance during the cycle at room temperature (25°C, 4C / 1C) was tested, see Table 1.
[0061] Comparative Example 5
[0062] A battery was made using a mixture of natural graphite, artificial graphite and hard carbon as the negative electrode, and the performance during the cycle at room temperature (25°C, 4C / 1C) was tested, see Table 1.
[0063] Table 1: The performance of the test during the cycle at room temperature (25°C, 4C / 1C) is as follows:
[0064]
[0065]
[0066] As shown in Table 1, although the capacity retention rate of carbonized natural graphite, artificial graphite and hard carbon is improved compared with that of natural graphite or artificial graphite alone when simply and directly blended, the capacity retention rate can be significantly improved by using electrospinning to make natural graphite, artificial graphite and hard carbon into nanofiber materials as the negative electrode of the battery.
[0067] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0068] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A method for preparing a negative electrode material, characterized in that: include Physically mixing hard carbon, carbonized natural graphite and carbonized artificial graphite to obtain a graphite mixed material; Adding graphite mixed material and polyacrylonitrile into water and stirring and mixing to obtain a spinning solution; The fiber film is obtained by electrospinning the spinning solution; The fiber film is placed at 180°C to 250°C and pre-oxidized in an air atmosphere to make it cross-linked; The pre-oxidized fiber film is slowly heated to 1000°C to 2500°C in an inert atmosphere for carbonization and then naturally cooled to obtain a nanofiber negative electrode material.
2. The method for preparing the negative electrode material according to claim 1, characterized in that: The mass ratio of carbonized natural graphite, carbonized artificial graphite and hard carbon in the graphite mixed material is 60-70 parts of carbonized natural graphite, 20-30 parts of carbonized artificial graphite and 1-10 parts of hard carbon.
3. The method for preparing the negative electrode material according to claim 1, characterized in that: The particle size D50 of carbonized natural graphite is 9-12 μm.
4. The method for preparing the negative electrode material according to claim 1, characterized in that: The particle size D50 of carbonized artificial graphite is 13-16 μm.
5. The method for preparing the negative electrode material according to claim 1, characterized in that: In the spinning solution, the concentration of carbonized natural graphite, carbonized artificial graphite and hard carbon graphite mixed material in the spinning solution is 65% to 95% by weight volume ratio, and the concentration of polyacrylonitrile PAN in the spinning solution is 5% to 35% by weight volume ratio.
6. The method for preparing the negative electrode material according to claim 1, characterized in that: During the electrospinning process using the spinning solution, the flow rate of the spinning solution is controlled to be 0.3-1.5 mL / h.
7. The method for preparing the negative electrode material according to claim 1, characterized in that: Add graphite mixed material and polyacrylonitrile into water and stir and mix for 10 to 20 hours; In the process of electrospinning using the spinning solution, the spinning solution is sucked into a syringe with a needle with an inner diameter of 0.3 to 1 mm, and the syringe is placed on a syringe pump to control the flow rate. The distance between the spinneret and the receiving plate is 10 to 25 cm, and the voltage between the plates is 15 to 35 kV. Spinning is carried out at room temperature to obtain a fiber film.
8. The method for preparing the negative electrode material according to claim 1, characterized in that: The fiber film is placed at 180°C to 250°C and pre-oxidized in an air atmosphere so that the cross-linking time is controlled to be 1.5 to 2.5 hours.
9. The method for preparing the negative electrode material according to claim 1, characterized in that: The pre-oxidized fiber film is slowly heated to 1000° C. to 2500° C. in an inert atmosphere at a speed of 2 to 5° C. / min.
10. The method for preparing the negative electrode material according to claim 1, characterized in that: The pre-oxidized fiber film is treated at 1000° C. to 2500° C. in an inert atmosphere for 2 to 10 hours.
11. A negative electrode of a battery, characterized in that: The battery negative electrode is prepared by the preparation method of the negative electrode material according to any one of claims 1-10.
12. A battery, characterized in that: It comprises a battery negative electrode, and the battery negative electrode is prepared by the preparation method of the negative electrode material according to any one of claims 1-10.
Citation Information
Patent Citations
Preparation method of composite negative electrode material of lithium ion battery
CN102683646A
High-safety fast-charging lithium ion battery negative electrode active material, negative electrode and lithium ion battery
CN108963185A
Lithium ion battery negative electrode material, negative electrode and lithium ion battery
CN112928274A
Lithium ion battery and preparation method thereof
CN114335687A
Lithium ion battery and energy storage device comprising same
CN115763740A
